Association between serum folate levels and schizophrenia based on sex. Issue 9 (30th June 2020) - Tomioka, Yukiko; Kinoshita, Makoto; Umehara, Hidehiro; Nakayama, Tomohiko; Watanabe, Shin‐ya; Nakataki, Masahito; Numata, Shusuke; Ohmori, Tetsuro
Abstract : Aim: Sex differences in serum folate concentrations are well known, but no studies have investigated the association between serum folate levels and schizophrenia based on sex. With this study in a Japanese population, we examined the difference in serum folate levels between patients with schizophrenia and non‐psychiatric controls stratified by sex. The relations among serum folate levels, plasma total homocysteine (tHcy), and serum vitamin B6 (pyridoxal) levels were also examined using data from our previous studies. Methods: The serum folate concentrations of 482 patients diagnosed with schizophrenia and 1350 non‐psychiatric control subjects were measured. We conducted an analysis of covariance to examine the differences in serum folate levels between the two groups based on sex. Spearman's rank correlation was used to evaluate the relations among folate, tHcy, and vitamin B6 levels. Results: In the control group, serum folate concentrations were higher in women than in men. Lower levels of serum folate were observed in both male and female patients with schizophrenia. An inverse correlation between serum folate and plasma tHcy and a weak positive correlation between serum folate and vitamin B6 were observed in the combined cohort. Conclusion: Our findings suggest that: (i) a low serum folate level may be associated with schizophrenia regardless of sex; and (ii) folate administration may be beneficial for the treatment of schizophrenia. In schizophrenic patients with low serum folate levels, folate administration might result in improvements in high tHcy and an increase in low vitamin B6 levels.